Design, Synthesis and Efficacy of Hybrid Triclosan‐gold Based Molecules on Artemisinin‐resistant Plasmodium falciparum and Leishmania infantum Parasites. Issue 2 (13th January 2020) - Ouji, Manel; Delmas, Sandra Bourgeade; Álvarez, Álvaro Fernández; Augereau, Jean‐Michel; Valentin, Alexis; Hemmert, Catherine; Gornitzka, Heinz; Benoit‐Vical, Françoise
Abstract: The emergence of resistant parasites, Plasmodium and Leishmania, responsible of malaria and leishmaniasis diseases, to the currently available drugs, remains one of the major threats to public health. Therefore, there is an urgent need to develop new molecules. Several hybrid molecules combining triclosan and gold(I) complexes have been synthesized and evaluated, in vitro, for their activities on P. falciparum and L. infantum parasites. The obtained results showed a good activity of the compounds. However, the cytotoxicity assays suggest a structure modulation to improve the selectivity. The synthesized molecules were also tested in a context of Plasmodium falciparum artemisinin‐resistance and the results showed no cross‐resistance induced between one gold(I) complex and artemisinin. This highlights that these compounds appear as a strong basis for further pharmacomodulation work to propose molecules targeting resistant parasites. Abstract : One molecule to target two pathologies. In the fight against major parasite diseases such as malaria and leishmaniasis, novel drugs active against drug‐resistant parasites are needed. Hybrid molecules combining triclosan and gold(I) complexes appear as a promising avenue.